Pengaruh “Viyo” Terhadap Pengetahuan Dan Dukungan Suami Pada Penggunaan Metode Kontrasepsi - Mekar Dwi Anggraeni; Nina Setiawati; Arlina Eka Agustin (Centre of Applied Science for Pharmaceutical Science Universitas Jenderal Soedirman, 2024)
Background : The use of contraceptive methods among husband in Indonesia is quite low. Husband’s knowledge and support affect contraceptive methods used significantly. Nurse plays an important role to increase husband’s knowledge and support by providing health education. Nowadays, health education using youtube becoming popular. This study aimed to examine the effect youtube video (Viyo) to increase husband's knowledge and support in using the contraceptive method. Methods : This study used a Quasi Experimental method. The sampling technique used simple random sampling which involved 19 repondents per group. Data collection was carried out on 22 January 2021 - 08 February 2021. The data were analyzed using univariate analysis, paired t test, and Wilcoxon test. Result: The majority of respondents in this study had 1 child (81,6%), aged 27,74 years old, graduated Junior High School (50%), farmer (52,6%) and had income of <Rp. 500,000 per month (50%). The results showed that there were significant differences between knowledge pretest and posttest (p=0,000) and husband's support (p=0,002). Conclusion: Health education using Viyo has a significant effect to increase the husband's knowledge and support in using the contraceptive method.